The Impact of Tourism Development on the Economy of the Community in Lerohoilim Village, Kei Besar District - Sindy Monika Metuduan; Rafael Marthinus Osok; Ferdinand Salomo Leuwol (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
Tourism development in Lerohoilim Village, Kei Besar District, Southeast Maluku, holds great potential for improving the local economy. However, the impacts of this development are not yet fully understood, particularly in the context of economic and social sustainability. This study employs a descriptive qualitative method, utilizing observation, interviews, and documentation for data collection. The findings reveal that tourism development has positive effects, such as increased income for the community through small and medium enterprises (SMEs) in accommodation, food stalls, and handicrafts. Furthermore, tourism creates new job opportunities for local residents. However, challenges remain in preserving the environment and local culture due to the surge in tourist visits. In conclusion, tourism development in Lerohoilim Village must continue to improve through sustainable planning and active community participation to ensure equitable economic benefits while preserving the local ecosystem and culture. The implication is that successful sustainable tourism development could serve as a model for other villages in Maluku.